A novel hydrophilic hydrogel with a 3D network structure for the highly efficient enrichment of N-glycopeptides. Issue 11 (5th May 2022) - Jin, Haozhou; Gao, Wenqing; Liu, Rong; Yang, Jiaqian; Zhang, Shun; Han, Renlu; Lin, Jing; Zhang, Sijia; Yu, Jiancheng; Tang, Keqi
Abstract : A novel super-hydrophilic hydrogel (ZIF-8/SAP) was first proposed and facilely fabricated to capture N -glycopeptides from complex biological samples with excellent selectivity and sensitivity. Abstract : Protein glycosylation is of great significance in various physiological processes. Nevertheless, it remains a huge challenge to identify glycopeptides in complex biosamples by the direct mass spectrometry analysis due to the low ion efficiency and low abundance of glycopeptides. In this study, a novel hydrogel (denoted as ZIF-8/SAP) with a stable three-dimensional (3D) network structure and excellent hydrophilicity was successfully fabricated to capture glycopeptides with high efficiency. Owing to the unique characteristics, ZIF-8/SAP exhibited great selectivity (1 : 1000), great sensitivity (1 fmol μL −1 ), large binding capacity (300 mg g −1 ) and satisfactory reusability (seven cycles). Inspired by the great enrichment performance of the as-prepared material toward glycopeptides, ZIF-8/SAP was further applied to capture glycopeptides from a real human serum sample. The experimental results demonstrated that 217 N -glycosylation sites were identified in 283 N -glycopeptides, corresponding to 95 glycoproteins identified from 10 μL human serum by the nano-LC-MS/MS analysis, revealing the great potential of the novel ZIF-8/SAP hydrogel for glycopeptide enrichment and glycoproteomic research.